How can the subjective well-being of nurses be predicted? Understanding the mediating effect of psychological distress, psychological resilience and emotional exhaustion - Anasori, Elham; Kucukergin, Kemal Gurkan; Soliman, Mohammad; Tulucu, Fadime; Altinay, Levent (Emerald Group Publishing Ltd, 2022)
Purpose This paper aims to examine the relationships among work-family conflict (WFC), cognitive regulation, psychological resilience (PR), psychological distress (PD), emotional exhaustion (EE) and subjective well-being (SWB) in a very complex model based on job demands-resources. Also, mediator roles of PD, PR and EE are analyzed. Design/methodology/approach Data for the study were collected from 158 full-time nurses working in two hospitals in North Cyprus. Partial Least Squares-Structural Equation Modelling (PLS-SEM) was used to test the model. Findings The authors' findings reveal that cognitive emotion regulation reduces employees' WFC. WFC also has a negative effect on employees' SWB directly and through the mediating role of EE. However, the role of PR in the relationship between cognitive emotion regulation and PD was not significant. Originality/value The study adds the original views for hospitals and service providers to recognize the factors which exert detrimental effects on employees' mental health and also the factors which help them to tackle the harsh situation specifically in the time of crisis. Theoretical and practical implications are provided in the study.
Keywords: Cognitive emotion regulation; Psychological resilience; Work-family conflict; Psychological distress; Emotional exhaustion; Subjective well-being